Preparation method of nano silver oxide aggregate particles, low-temperature conductive silver paste and preparation method of low-temperature conductive silver paste

By using alcohol solutions and surfactants in conductive materials to promote the formation and dispersion of nano silver oxide particles, combined with silver powder, the problem of high-temperature reduction of silver oxide particles is solved, and low-temperature sintering and high-conductive properties are achieved.

CN119219051APending Publication Date: 2024-12-31SOUTHEAST UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310772343.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31

Smart Images

  • Figure CN119219051A_ABST
    Figure CN119219051A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of nano silver oxide aggregate particles, low-temperature conductive silver paste and a preparation method of the low-temperature conductive silver paste. The preparation method of the aggregate particles comprises the following steps: preparing a silver salt solution, mixing an alcoholic solution with an alkali solution to prepare a mixed solution, then gradually dropwise adding the silver salt solution into the mixed solution for reaction, and filtering and drying a product to prepare the aggregate particles. The nano silver oxide aggregate particles are simple to prepare, a small amount of alcohol is added in the synthesis process, and hydroxyl is contained in the molecular structure of the alcohol and can wrap the surfaces of a plurality of small particles, so that connection among the small particles is enhanced, and the silver oxide aggregate is formed. The uniqueness of the morphology is that the reduction temperature of the silver oxide can be greatly reduced, and feasibility is provided for low-temperature sintering of the conductive paste containing the silver oxide. And the addition proportion of silver oxide and silver particles in the conductive silver paste is regulated and controlled to obtain a paste formula with excellent performance. The conductive paste composed of the nano silver oxide and the nano silver shows excellent conductive performance at low temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing nanoparticles, conductive paste and a preparation method thereof, and in particular to a method for preparing nano silver oxide aggregate particles, low-temperature conductive silver paste and a preparation method thereof. Background Art

[0002] With the continuous development of electronic information technology, the demand for various conductive materials is also increasing. Conductive paste, as one of the most studied materials, has been used as a printed electrode material for various electronic devices, such as displays, sensors, antennas, solar cells, etc. Conductive paste is an organic / inorganic multi-component hybrid composite material containing conductive fillers. The conductivity of the paste after sintering is closely related to the conductive filler. At present, the conductive filler with the best electrical and thermal conductivity is silver powder, but the conductive filler has the disadvantages of high cost, easy migration of silver ions and high sintering temperature, which limits its application in flexible electronic devices. In order to solve the problem of high sintering temperature of the paste, silver precursor is used to partially replace silver powder as a conductive filler, and sintering is carried out after uniform mixing.

[0003] Silver oxide (Ag2O) is a dark brown powder and the most thermodynamically stable and common oxide powder in silver. Silver oxide particles are reduced to metallic silver under sintering. These reduced silver oxides can reduce the contact resistance between silver powders and fill the gaps between silver powders to form a dense conductive path and improve the conductive properties of the paste. However, there are few researches on silver oxide electronic pastes. At the same time, there are a series of problems such as high self-reduction temperature of silver oxide particles, incomplete reduction of silver oxide particles, and high sintering porosity of silver paste, which limit the application of silver oxide in low-temperature sintering electronic pastes. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a method for preparing nano silver oxide aggregate particles with low self-reduction temperature and high reduction degree;

[0005] The second object of the present invention is to provide a low-temperature conductive silver paste;

[0006] The third object of the present invention is to provide a method for preparing the above-mentioned low-temperature conductive silver paste.

[0007] Technical solution: The method for preparing nano silver oxide aggregate particles of the present invention comprises the following steps:

[0008] (1) preparing a silver salt solution;

[0009] (2) Mixing the alcohol solution, the surfactant and the alkali solution to prepare a mixed solution:

[0010] (3) gradually adding the silver salt solution dropwise to the mixed solution for reaction, filtering and drying the product to obtain the nano silver oxide aggregate powder.

[0011] The molar ratio of the silver salt to the alkali is 1:1 to 1:2, and specifically can be 1:1, 1:1.3, 1:1.5, 1:1.7, 1:2. The mass concentration of the silver salt solution is 1.7 g / 25 ml to 1.7 g / 300 ml. According to the different mass concentrations, the mass of the silver salt is kept unchanged and the volume of the aqueous solution is changed. More preferably, the mass of the silver salt is determined to be 1.7 g, the amount of the silver salt is 0.01 mol, and the volume of the water is adjusted to 25 ml-300 ml.

[0012] The mass concentration of the alkali solution is 0.56g-1.12g / 22ml; specifically, the mass concentration of the alkaline substance can be selected to be 0.56g / 22ml, 0.738g / 22ml, 0.84g / 22ml, 0.952g / 22ml, or 1.12g / 22ml.

[0013] The silver salt may be any of various silver salts commonly used in the art. Preferably, the silver salt is one or more of silver nitrate, silver oxalate, silver acetate, and silver carbonate. More preferably, the silver salt is silver nitrate or silver oxalate. Particularly preferably, the silver salt is silver nitrate.

[0014] Wherein, the alkali is one or more of sodium hydroxide, potassium hydroxide and ammonia water; more preferably, the alkali is potassium hydroxide.

[0015] Wherein, in step (2), the alcohol is at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, and ethylene glycol; the mass concentration of the alcohol solution is 0.5-2g / 22ml, more preferably, the mass concentration is 1g-2g / 22ml.

[0016] Wherein, in step (2), the surfactant is at least one of polyvinyl pyrrolidone, polyethylene glycol 400, polyvinyl alcohol, gelatin, gum arabic, sodium lauryl sulfate, and oleic acid; preferably at least one of polyvinyl pyrrolidone, polyethylene glycol 400, gelatin, and gum arabic; the mass ratio of the surfactant to the alkali is 0.05-0.25, and more preferably, the mass ratio is 0.05-0.2.

[0017] Wherein, in step (3), the reaction temperature is 35-85°C and the reaction time is 1-4h.

[0018] Wherein, in step (3), the product is repeatedly washed with ethanol and water for three times and filtered, and vacuum dried at 45° C.-55° C. for 12 hours to obtain nano silver oxide aggregate particles.

[0019] The particle size of the prepared nano silver oxide aggregate particles is 100-500 nm, more preferably 50-200 nm.

[0020] The low-temperature conductive silver paste of the invention comprises, by mass percentage, 10%-70% of nano silver oxide aggregate powder prepared by the above method, 10%-70% of silver powder and 20% of organic carrier.

[0021] The silver powder is one or more of 500nm spherical silver powder, 600nm spherical silver powder, 800nm ​​spherical silver powder, 1.3μm flake silver powder, 1.5μm flake silver powder, and 2.0μm flake silver powder.

[0022] Preferably, in the organic carrier, the solvent is one or two of terpineol, tributyl phosphate, ethylene glycol ethyl ether acetate, and turpentine, accounting for 75%-90% of the mass percentage of the organic carrier.

[0023] Preferably, in the organic carrier, the binder is one or more of dibutyl phthalate, phenoxy resin, epoxy resin, and acrylic resin, accounting for 5%-20% of the mass percentage of the organic carrier.

[0024] The method for preparing the above-mentioned low-temperature conductive silver paste comprises the following steps:

[0025] (1) uniformly mixing nano silver oxide aggregate particles and silver powder;

[0026] (2) mixing the solvent and the binder in the organic vehicle, heating, and stirring thoroughly until a transparent colloid is formed;

[0027] (3) Grinding and mixing the powder mixed in step (1) and the colloid in step (2) to form a printable paste.

[0028] Specifically, in step (1), the mixing time is 1-2 hours; in step (2), the mixture is heated to 60-80° C. in a water bath and stirred for 4-10 hours until a uniform, transparent colloid is formed.

[0029] The performance test of the conductive paste includes paste sintering: the prepared paste is printed on a flexible substrate by screen printing, and sintered at 140-220°C for 1-2 hours, and finally its conductive performance is tested. Among them, the conductive paste containing nano silver oxide aggregate particles has a cross-linked paste surface after sintering at 160°C for 1 hour, and the formed conductive path has a high density. This is because the nano silver oxide aggregate particles self-reduced to fill the gap between the silver powder.

[0030] Principle of the invention: Due to the effect of the alcohol solution, alcohol can promote the formation of silver oxide aggregate particles and prevent the growth of single silver oxide particles. The reason is that alcohol contains hydroxyl groups in its molecular structure, which can wrap the surface of the particles during the synthesis process, promote the aggregation of small particles, and enhance the dispersibility of the particles. The obtained nano silver oxide aggregate particles are evenly dispersed and small in size. Small protrusions are clearly observed on the surface of the particles. The form of particle aggregates allows silver oxide to be reduced to silver at a lower temperature.

[0031] When silver salt solution is added dropwise to alcohol solution and surfactant solution simultaneously, the surfactant of these nonionic polymers can reduce the aggregation of nanoparticles by the repulsive force produced by hydrophobic carbon chains, and these carbon chains can extend into the solvent and interact with each other, so due to the spatial site resistance effect, the distance between particles is prolonged, thereby playing a dispersive effect. In addition, the surfactant can be attached to specific particle surfaces, promote the growth of specific crystal surfaces, and hinder the growth of other crystal surfaces, thereby realizing morphological control. Meanwhile, alcohol and the surfactant of these nonionic polymers can play a certain synergistic effect, and can also control the morphology of particles in promoting the formation of silver oxide aggregate particles, and the nano silver oxide aggregate particles obtained have uniform morphology and excellent dispersibility.

[0032] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects: (1) Due to the effect of the alcohol solution, alcohol can promote the formation of silver oxide aggregate particles and prevent the growth of single silver oxide particles. The obtained nano silver oxide aggregate particles are evenly dispersed and have a small particle size. Small protrusions are clearly observed on the surface of the particles. The form of the particle aggregates enables silver oxide to be reduced to silver at a lower temperature, and the degree of reduction is high. (2) When the silver salt solution is simultaneously added to the alcohol solution and the surfactant solution, it plays a dispersing role and realizes morphological control. While promoting the formation of silver oxide aggregate particles, the morphology of the particles can also be controlled. The obtained nano silver oxide aggregate particles have uniform morphology and excellent dispersibility. (3) The conductive paste obtained by uniformly mixing the nano silver oxide aggregate particles and silver powder of the present invention can form a dense conductive path at a lower temperature. Therefore, excellent electrical properties can be obtained under low temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a scanning electron microscope image of the nano silver oxide aggregate particles obtained in Example 1;

[0034] Figure 2 is the XRD pattern of the nano silver oxide aggregate particles obtained in Example 1;

[0035] Figure 3 This is a scanning electron microscope image of the conductive paste obtained in Example 1 sintered at 160° C. for 1 hour. DETAILED DESCRIPTION

[0036] The present invention is described in further detail below.

[0037] Example 1

[0038] Preparation of nano silver oxide aggregate particles: First, add 1g of n-butanol to 0.56g / 22ml of potassium hydroxide solution to prepare an alkaline solution containing alcohols. Then, under the conditions of 55°C and magnetic stirring, gradually add 1.7g / 100ml of silver nitrate solution to the alkaline solution for reaction. After the silver nitrate solution is added, the reaction time is 2h. During the addition of the silver nitrate solution, a brown precipitate is gradually generated. After the reaction is completed, wash it repeatedly with ethanol and water for 3 times and filter it. The obtained product is vacuum dried at 50°C for 12h to obtain dark brown nano silver oxide aggregate particles.

[0039] Figure 1 is a scanning electron microscope image of nano silver oxide aggregate particles obtained in Example 1. Figure 1 It can be seen that the nano silver oxide aggregate particles obtained in this Example 1 are spherical and have a particle size of 50-200 nm. Figure 2 is the XRD pattern of the nano silver oxide aggregate particles obtained in Example 1. Figure 2 It can be seen that the nano silver oxide aggregate particles obtained in this Example 1 are hexahedral silver oxide crystals and no other impurities are generated.

[0040] Preparation of low-temperature conductive slurry: Weigh 1g of homemade nano silver oxide aggregate particles, 1g of 600nm spherical silver powder, 0.025g of organic carrier, and pineneol as organic solvent. Add them according to the fluidity of the slurry, with a specific addition amount of 0.3g. Grind and mix evenly to obtain low-temperature conductive slurry S1.

[0041] According to different sintering temperatures, the relationship between the sintering temperature and the average resistivity of the S1 slurry is obtained as shown in Table 1. It can be seen from the table that the slurry has excellent conductive properties at 160°C.

[0042] Table 1

[0043] Slurry sintering temperature / ℃ Average resistivity / μΩ·cm 140 38.3 160 20 180 19 200 16 220 16.67

[0044] Figure 3 It is the surface of low temperature conductive paste sintered at 160℃. Figure 3 It can be seen that the conductive paste can form a dense conductive path at a relatively low temperature.

[0045] Example 2

[0046] Preparation of nano silver oxide aggregate particles: First, add 0.5g of methanol to 0.738g / 22ml of potassium hydroxide solution to prepare an alkaline solution containing alcohols. Then, under the conditions of 35°C and magnetic stirring, gradually add 1.7g / 25ml of silver nitrate solution to the alkaline solution for reaction. After the silver nitrate solution is added, the reaction time is 2h. During the addition of the silver nitrate solution, a brown precipitate is gradually generated. After the reaction is completed, wash it repeatedly with ethanol and water for 3 times and filter it. The obtained product is vacuum dried at 45°C for 12h to obtain dark brown nano silver oxide aggregate particles.

[0047] Preparation of low-temperature conductive slurry: Weigh 1g of homemade nano-silver oxide aggregate particles, 1g of 600nm spherical silver powder, 0.025g of organic carrier, and pineneol as organic solvent. Add them according to the fluidity of the slurry, with a specific addition amount of 0.3g. Grind and mix evenly to obtain low-temperature conductive slurry S2.

[0048] Example 3

[0049] Preparation of nano silver oxide aggregate particles: First, add 1g of isopropanol to 0.84g / 22ml potassium hydroxide solution to prepare an alkaline solution containing alcohol. Then, under the conditions of 45°C and magnetic stirring, gradually add 1.7g / 150ml of silver nitrate solution to the alkaline solution for reaction. After the silver nitrate solution is added, the reaction time is 2h. During the addition of the silver nitrate solution, a brown precipitate is gradually generated. After the reaction is completed, wash it repeatedly with ethanol and water for 3 times and filter it. The obtained product is vacuum dried at 55°C for 12h to obtain dark brown nano silver oxide aggregate particles.

[0050] Preparation of low-temperature conductive slurry: Weigh 1g of homemade nano silver oxide aggregate particles, 1g of 600nm spherical silver powder, 0.025g of organic carrier, and pineneol as organic solvent. Add them according to the fluidity of the slurry, with a specific addition amount of 0.3g. Grind and mix evenly to obtain low-temperature conductive slurry S3.

[0051] Example 4

[0052] Preparation of nano silver oxide aggregate particles: First, add 1.5g of n-butanol to 0.952g / 22ml potassium hydroxide solution, and then add polyvinyl pyrrolidine with a mass ratio of 0.05 to the alkali to prepare an alkaline solution containing alcohols and surfactants. Then, under the conditions of 65°C and magnetic stirring, 1.7g / 200ml of silver nitrate solution is gradually added dropwise to the alkaline solution for reaction. After the silver nitrate solution is added dropwise, the reaction time is 2h. During the addition of the silver nitrate solution, a brown precipitate is gradually generated. After the reaction is completed, it is washed repeatedly with ethanol and water for 3 times and then filtered. The obtained product is vacuum dried at 50°C for 12h to obtain dark brown nano silver oxide aggregate particles.

[0053] Preparation of low-temperature conductive slurry: Weigh 1g of homemade nano silver oxide aggregate particles, 1g of 600nm spherical silver powder, 0.025g of organic carrier, and pineneol as organic solvent. Add them according to the fluidity of the slurry, with a specific addition amount of 0.3g. Grind and mix evenly to obtain low-temperature conductive slurry S4.

[0054] Example 5

[0055] Preparation of nano silver oxide aggregate particles: First, add 2g of ethanol to 1.12g / 22ml potassium hydroxide solution, and then add polyethylene glycol with a molecular weight of 400 at a mass ratio of 0.2 to the alkali to prepare an alkaline solution containing both alcohols and surfactants. Then, under the conditions of 85°C and magnetic stirring, 1.7g / 300ml of silver nitrate solution is gradually added dropwise to the alkaline solution for reaction. After the silver nitrate solution is added dropwise, the reaction time is 2h. During the addition of the silver nitrate solution, a brown precipitate is gradually generated. After the reaction is completed, it is washed repeatedly with ethanol and water for 3 times and then filtered. The obtained product is vacuum dried at 50°C for 12h to obtain dark brown nano silver oxide aggregate particles.

[0056] Preparation of low-temperature conductive slurry: Weigh 1g of homemade nano silver oxide aggregate particles, 1g of 600nm spherical silver powder, 0.025g of organic carrier, and pineneol as organic solvent. Add them according to the fluidity of the slurry, with a specific addition amount of 0.3g. Grind and mix evenly to obtain low-temperature conductive slurry S5.

[0057] According to different preparation methods of nano silver oxide aggregate particles, the relationship between the slurry sintered at 160°C and different slurries is obtained as shown in Table 2. It can be seen from Table 2 that the resistivity of S1 and S4 slurries is lower.

[0058] Table 2

[0059] Slurry type Average resistivity / μΩ·cm S1 20 S2 39 S3 25.3 S4 13.67 S5 34

[0060] Comparative Example 1

[0061] Nano silver oxide aggregate particles were prepared according to the method of Example 1, except that the homemade nano silver oxide aggregate particles were not weighed, only 2 g of 600 nm spherical silver powder was added, and the remaining slurry addition amounts remained unchanged. The obtained slurry was named D1.

[0062] Comparative Example 2

[0063] Nano silver oxide aggregate particles were prepared according to the method of Example 1, except that 0.4 g of homemade nano silver oxide aggregate particles and 1.6 g of 600 nm spherical silver powder were weighed, and the amounts of other slurry additions remained unchanged. The obtained slurry was named D2.

[0064] Comparative Example 3

[0065] Nano silver oxide aggregate particles were prepared according to the method of Example 1, except that 0.5 g of homemade nano silver oxide aggregate particles and 1.5 g of 600 nm spherical silver powder were weighed, and the amounts of other slurry additions remained unchanged. The obtained slurry was named D3.

[0066] Comparative Example 4

[0067] Nano silver oxide aggregate particles were prepared according to the method of Example 1, except that 0.7 g of homemade nano silver oxide aggregate particles and 1.3 g of 600 nm spherical silver powder were weighed, and the amounts of other slurry added remained unchanged. The obtained slurry was named D4.

[0068] According to the different amounts of nano silver oxide aggregate particles added to the slurry, four groups of comparative experiments were obtained.

[0069] The resistivity change after sintering at 160°C is shown in Table 3. As can be seen from Table 2, adding too much or too little nano silver oxide aggregate particles will affect the conductive properties of the slurry.

[0070] Table 3

[0071] Silver paste type Average resistivity / μΩ·cm S1 20 D1 56 D2 15 D3 14 D4 14

[0072] The method for preparing nano silver oxide aggregate particles of the present invention is simple to operate and convenient for large-scale production, and the conductive paste obtained by uniformly mixing the nano silver oxide aggregate particles prepared by the method with silver powder has excellent electrical properties.

Claims

1. A method for preparing nano silver oxide aggregate particles, characterized in that it comprises the following steps: (1) preparing a silver salt solution; (2) Mixing the alcohol solution and the alkali solution to obtain a mixed solution: (3) gradually adding the silver salt solution dropwise into the mixed solution to react, filtering and drying the product to obtain the nano silver oxide aggregate powder.

2. The method for preparing nano silver oxide aggregate particles according to claim 1, characterized in that: In step (2), the alcohol solution is mixed with an alkali solution and a surfactant to prepare a mixed solution.

3. The method for preparing nano silver oxide aggregate particles according to claim 1, characterized in that: In step (3), the reaction temperature is 35-85°C and the reaction time is 1-4h.

4. The method for preparing nano silver oxide aggregate particles according to claim 1, characterized in that: In step (2), the alcohol is at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol and ethylene glycol.

5. The method for preparing nano silver oxide aggregate particles according to claim 1, characterized in that: In step (2), the mass concentration of the alcohol solution is 0.5-2g / 22ml.

6. The method for preparing nano silver oxide aggregate particles according to claim 1, characterized in that: In step (2), the surfactant is at least one of polyvinyl pyrrolidone, polyethylene glycol 400, polyvinyl alcohol, gelatin, gum arabic, sodium lauryl sulfate, and oleic acid.

7. The method for preparing nano silver oxide aggregate particles according to claim 2, characterized in that: The mass ratio of the surfactant to the alkali is 0.05-0.

25.

8. The method for preparing nano silver oxide aggregate particles according to claim 1, characterized in that: The molar ratio of the silver salt to the base is 1:1 to 1:

2.

9. A low-temperature conductive silver paste, characterized in that: The invention comprises, by mass percentage, 10%-70% of nano silver oxide aggregate particles prepared by the method according to claim 1, 10%-70% of silver powder and 20% of organic carrier.

10. A method for preparing the low-temperature conductive silver paste according to claim 9, characterized in that: The steps include: (1) uniformly mixing nano silver oxide aggregate particles and silver powder; (2) mixing the solvent and the binder in the organic vehicle, heating, and stirring thoroughly until a transparent colloid is formed; (3) Grinding and mixing the powder mixed in step (1) and the colloid in step (2) to form a printable paste.

Citation Information

Cited By

  • High-temperature-resistant conductive paste and preparation method thereof

    CN121306633A